THE IMPACT OF LANGUAGE IN THE TEACHING AND LEARNING OF MATHEMATICS AT JUNIOR SECONDARY SCHOOL IN KATSINA - ABUBAKAR, HAMZA; UMAR, SANI ABUBAKAR; MUSAWA, BASIRU IBRAHIM (IJRDO -JOURNAL OF MATHEMATICS, 2015)
The purpose of this research was to determine the effect of Language on Junior Secondary students’ academic performance in mathematics. Participants were 120 students, purposefully sampled among Junior Secondary one (JSSI) students of Government Science Secondary School Dutsin-Ma, Katsina in Nigeria. Data collection occurred before and after proper teaching(in Hausa) for 12 weeks. two research question were formulated to guide this study. The statistical analysis showed there was a significant difference before and after the teaching in Hausa on students Performance in Mathematics (p≤ 0.05). Based on the findings, it was recommended among the other things that home Language (mother-tongue) should be adopted in our school system particularly at Junior secondary schools in Nigeria as it will improve students’ performance in Mathematic towards sustainable development in Nigeria